2017
DOI: 10.1016/j.apsb.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1 H NMR-based metabolomics for discrimination of different parts and development of a new processing workflow for Cistanche deserticola

Abstract: Cistanche deserticola (CD) is one of the two authoritative source plants of Cistanches Herba, a well-known medicinal plant. Herein, 1H NMR spectroscopy was employed to characterize the chemical profile and to distinguish the different parts, as well as to propose a new processing workflow for CD. Signal assignment was achieved by multiple one and two dimensional NMR spectroscopic techniques in combination with available databases and authentic compounds. The upper parts of the plant were distinguished from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…There are fewer studies to clarify the chemical characteristics in different parts and growth stages of P. notoginseng plants. Metabolomics is a scientific study that reveals metabolite differences for authentication of species 13 , 14 , 15 , 16 , 17 differentiation of cultivation regions 18 , 19 , age discrimination 20 , 21 , and discrimination of raw and processed samples 22 . Thus, the chemical characteristics of saponins in the aerial and underground parts of 2- and 3-year-old P. notoginseng plants could be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer studies to clarify the chemical characteristics in different parts and growth stages of P. notoginseng plants. Metabolomics is a scientific study that reveals metabolite differences for authentication of species 13 , 14 , 15 , 16 , 17 differentiation of cultivation regions 18 , 19 , age discrimination 20 , 21 , and discrimination of raw and processed samples 22 . Thus, the chemical characteristics of saponins in the aerial and underground parts of 2- and 3-year-old P. notoginseng plants could be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that ITS2 could not be amplified from Angelicae Sinensis Radix extract or decoctions boiled for more than 120 min (Wang et al, 2016a ). According to traditional technologies and the Chinese Pharmacopoeia Commission ( 2015 ), Cistanches Herba is always highly processed to increase its medicinal efficacy; these processes, include oven drying, salting and steaming with wine (Zou et al, 2017 ), which lead to DNA degradation. In addition, various excipients are added during processing, such as honey, starch, and dextrin.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in comparison of phytochemical purifications, more components are usually identified by applying the proposed mass fragmentation pathways to LC–MS/MS datasets. Some other instrumentation, such as NMR spectroscopy, 87–89 and infrared spectroscopy, 90–95 serve as the complementary roles. Our group reviewed the research progress regarding chemical analysis of CH a couple of years ago 9 ; consequently, we herein underline merely the investigations featured with confirmative and/or large‐scale chemical analysis, most of which occurred in the latest 10 years.…”
Section: In‐depth Qualitative and Quantitative Analyses Of Chemical Cmentioning
confidence: 99%